Artikulasi Kekerasan dalam Polemik Nasab: Analisis Wacana Fuad Plered dan Rizieq Syihab - Makyun Subuki; Mohammad Siddiq; Syihaabul Hudaa; Akhmad Saehudin (Aksara, 2025)
This study aims to analyze the discourse of violence in the public statements of two controversial Indonesian figures, Fuad Plered and Rizieq Syihab, who were involved in the polemic surrounding the Baʿalawi lineage. Employing a Critical Discourse Analysis (CDA) approach grounded in the theories of ideology and symbolic power. This research examines how abusive language, animal metaphors, and calls to violence are used to legitimize ideological positions and construct collective identities. The data were obtained from videos and social media posts containing the statements of both figures. The findings reveal that the Baʿalawi lineage polemic, which initially concerned genealogical-religious issues, has evolved into an arena of symbolic power articulation that produces identity dichotomies such as “indigenous” versus “sayyid” and narratives of betrayal against the nation. Through aggressive rhetoric involving expressions like “kill,” “deradicalization,” and calls for “war,” both figures construct a common enemy and reinforce social polarization based on religious identity. The study concludes that language serves as a central instrument in the production of ideology and functions as a form of symbolic violence within Indonesia’s religious public sphere. AbstrakPenelitian ini bertujuan untuk menganalisis wacana kekerasan dalam pernyataan publik dua tokoh kontroversial di Indonesia, Fuad Plered dan Rizieq Syihab, yang terlibat dalam polemik nasab kelompok Ba‘alawi. Menggunakan pendekatan Analisis Wacana Kritis (AWK) dengan landasan teori ideologi dan kekuasaan simbolik. Penelitian ini menelaah bagaimana bahasa makian, metafora hewan, dan seruan kekerasan digunakan untuk melegitimasi posisi ideologis serta membentuk identitas kolektif. Data penelitian diperoleh dari video dan unggahan media sosial yang memuat ujaran kedua tokoh tersebut. Hasil analisis menunjukkan bahwa polemik nasab yang semula bersifat genealogis-keagamaan telah berkembang menjadi arena artikulasi kekuasaan simbolik yang memunculkan dikotomi identitas “pribumi” versus “sayyid” dan narasi pengkhianatan terhadap bangsa. Melalui retorika agresif seperti diksi “bunuh”, “deradikalisasi”, dan seruan “perang”, kedua tokoh mengonstruksi musuh bersama dan memperkuat polarisasi sosial berbasis identitas keagamaan. Penelitian ini menegaskan bahwa bahasa berperan sentral dalam produksi ideologi dan berpotensi menjadi instrumen kekerasan simbolik di ruang publik keagamaan.